1998
DOI: 10.1097/00005392-199809020-00052
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Among Hormone Levels, Sperm Parameters and Paternity in Formerly Unilaterally Cryptorchid Men

Abstract: FSH levels are significantly higher and sperm counts are significantly lower in formerly cryptorchid men than in controls. In the cryptorchidism group the same differences are found in fertile and infertile men. Thus, elevated FSH and low sperm counts may be considered risks for infertility in formerly cryptorchid men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 6 publications
3
15
0
Order By: Relevance
“…In the formerly unilaterally cryptorchid segment of our cohort, we found that FSH levels were significantly higher and sperm counts significantly lower as compared to controls [16]. This same report also found that baseline LH and testosterone levels were not different between unilateral cryptorchids and controls, and this result is consistent with earlier reports of LH and testosterone levels being normal in both formerly bilaterally and unilaterally cryptorchid men [14, 15, 16]. …”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the formerly unilaterally cryptorchid segment of our cohort, we found that FSH levels were significantly higher and sperm counts significantly lower as compared to controls [16]. This same report also found that baseline LH and testosterone levels were not different between unilateral cryptorchids and controls, and this result is consistent with earlier reports of LH and testosterone levels being normal in both formerly bilaterally and unilaterally cryptorchid men [14, 15, 16]. …”
Section: Introductionsupporting
confidence: 92%
“…These levels correlate highly with sperm density. In two earlier publications by our group, correlations between inhibin B, FSH, and sperm density were highly significant, and showed that damage to the seminiferous tubules caused by cryptorchidism is reflected in both the hormone levels and semen analyses [16, 20]. The potential for measurement of hormone levels in formerly cryptorchid men and their ability to predict risk of fertility is potentially useful, since it is notoriously difficult to get men to donate semen, while a simple blood draw is often possible to get as part of a clinic visit.…”
Section: Discussionmentioning
confidence: 99%
“…Paternity for these men differed markedly from previously bilaterally cryptorchid men, among whom 38% were unable to father a child [2]. Also, initial analysis of hormonal levels and sperm parameters indicated higher follicle-stimulating hormone (FSH) levels and lower sperm counts [3]. FSH levels and sperm counts were inversely correlated.…”
Section: Introductionmentioning
confidence: 99%
“…Sex hormones in¯uence the development of prostate cancer, now the commonest cancer in men in some Western countries (Parkin et al 1992). Sex hormones also in¯uence a variety of other conditions in men, such as infertility (Kaiser et al 1988), low sperm count (Lee et al 1998;Liu et al 1999), and benign prostatic hyperplasia (Denis et al 1999). Diet-related changes in hormone metabolism may also be of interest to elite athletes, who may bene®t from maximising anabolic steroid production to enhance physical performance (Brotherhood, 1984;Miller & Wolfe, 1999).…”
Section: Introductionmentioning
confidence: 99%